A Riemann–Hilbert approach for the modified short pulse equation. Issue 9 (4th July 2019) - Guo, Boling; Liu, Nan
ABSTRACT: We present a Riemann–Hilbert approach for the modified short pulse equation q xt = q + 1 2 q ( q 2 ) xx on the line. This approach allows us to give a representation of the solution to the Cauchy problem, which can be efficiently used in studying its long-time behavior, also to describe the soliton solutions.